Addition Effect of Red Dragon Fruit Peel Powder (Hylocereuspolyrhizus) on the Characteristics of Young Coconut Jam (Cocos Nucifera) - Rina Yenrina; Rini Rini; Afissa Rahmadia (Lembaga Penelitian dan Pengabdian, Universitas Andalas, 2023)
The aim of this study to determine the addition effect of red dragon fruit peel powder on the physical and chemical quality characteristics of young coconut jam and get out the right concentration of making young coconut jam on sensory analysis.This study used a completely randomized design with 5 treatments and 3 replications. The research data were analyzed statistically using ANOVA and continued with the Duncan' New Multiple Range Test (DNMRT) at the 5% level. The treatment in this study was the addition of red dragon fruit peel powder with a concentration of 4% (treatment A), 12% (treatment B), 20% (treatment C), 28% (treatment D) and 36% (treatment E). The results showed that the addition of red dragon fruit peel powder had a significant effect on water content, ash content, pH, total dissolved solids, total sugar, Vitamin C, antioxidant activity and betacyanin.